The lost fairy tales - James, Anna (Anna Lois) (James, Anna (Anna Lois). Pages and Co., 2020)
When eleven-year-old Tilly Pages joins Oskar and his family on a Christmas trip to Paris, she and her friend bookwander into the land of fairy tales, where someone--or something--is causing chaos.